2020
DOI: 10.1038/s41419-020-2352-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of circRACGAP1 sensitizes gastric cancer cells to apatinib via modulating autophagy by targeting miR-3657 and ATG7

Abstract: The positive results of the apatinib phase III trial have cast new light on treatment for patients with advanced gastric cancer (GC). However, in terms of safety, apatinib toxicities may lead to a dose modification or treatment interruption. Therefore, proper intervention is urgently needed to help patients benefit from apatinib treatment. In this study, we found that apatinib promoted autophagy activation via upregulation of ATG7 expression and autophagy inhibition enhanced apatinib-induced apoptosis. With mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 58 publications
0
34
0
1
Order By: Relevance
“…A through inhibition of miR-198 and up-regulation PIK3R1. Ma, et al 23 revealed that circRACGAP1 enhances resistance to apatinib in GC cells through modulation of autophagy via regulating a miR-3657/ATG7 pathway. Furthermore, research has revealed that circPRRX1 expedites the development of esophageal cancer by binding to miR-1294 and up-regulating LASP1.…”
Section: Discussionmentioning
confidence: 99%
“…A through inhibition of miR-198 and up-regulation PIK3R1. Ma, et al 23 revealed that circRACGAP1 enhances resistance to apatinib in GC cells through modulation of autophagy via regulating a miR-3657/ATG7 pathway. Furthermore, research has revealed that circPRRX1 expedites the development of esophageal cancer by binding to miR-1294 and up-regulating LASP1.…”
Section: Discussionmentioning
confidence: 99%
“…As circRNA has the characteristics of stability and tissue specificity, thus it may become a tumor marker and be involved in progression of gastric cancer. Present study shows that Circ_0032821 promotes gastric cancer development by activating the MEK1/ ERK1/ 2; CircMRPS35 inhibits the progression of gastric cancer; Silencing RACRACGAP1 can enhance the sensitivity to Apatinib by targeting miR‐3657; CircRNA_0005075 inhibits gastric cancer growth via miR‐431/ p53/ epithelial stromal transformation axis; circ_0006282 promotes gastric cancer growth through miR‐155/ FBXO22 axis 11‐15 …”
Section: Discussionmentioning
confidence: 72%
“…CDDP, MTA, PTX, and oxaliplatin (OXA) are commonly used in gastric cancer (GC) chemotherapy [ 136 138 ]. However, patients always acquire chemotherapeutic resistance after treatment, which limits the overall clinical efficacy of the treatment.…”
Section: Mechanisms Of Circrnas In Drug Resistancementioning
confidence: 99%
“…Zhang et al found that circCCDC66 is an important regulator of CDDP resistance and is highly expressed in CDDP-resistant cells and tissues. In vitro and in vivo experiments showed that circCCDC66 inhibits apoptosis and promotes drug resistance by targeting miR-618 and releasing B cell lymphoma-2 (BCL2) [ 136 ]. Via microarray analysis, Xu et al identified the upregulation of circMTHFD2, which bound directly to miR-124 as a molecular sponge, in GC cells.…”
Section: Mechanisms Of Circrnas In Drug Resistancementioning
confidence: 99%